Comparison of Various Local Anesthetics During Conversion of Epidural Analgesia in Childbirth to Anesthesia During Cesarean Section - Yu. S. Aleksandrovich; D. I. Karabaev; O. V. Ryazanova; S. N. Nezabudkin; F. R. Barakaeva (Вестник анестезиологии и реаниматологии)
The objective: to estimate efficiency of local anesthetics in the conversion of epidural analgesia during physiological childbirth into anesthesia for emergency surgery for delivery.Subjects and Methods: A randomized prospective study was conducted. The patients were divided into three groups depending on the local anesthetic being used. In the first group (n = 49), 2% solution of lidocaine was administered in combination with 0.1 mg of adrenaline, in the second group (n = 48) – 0.5% bupivacaine, in the third group (n = 46) ‒ 0.75% ropivacaine. The study evaluated the onset rate, level, duration of the sensorimotor block, the severity of the pain syndrome, and revealed the frequency of unsuccessful conversion.Results: In the 1st group, the conversion was not success in 16.3% of women, in the 2nd group ‒ in 14.6%, and in the 3rd ‒ 10.9% of cases, due to that general anesthesia was used. When assessing the pain syndrome, the minimum score on the VAS scale 3 hours after surgery was observed with ropivacaine use. The fastest sensory block developed when using 2% lidocaine solution in combination with adrenaline. The motor block preserved for the longest time after administration of bupivacaine, in this regard, patients from the 2nd group began to activate later.Conclusions. The use of 0.5% bupivacaine solution as a local anesthetic during the conversion of epidural analgesia into anesthesia provides a sufficient level of anesthesia that allows surgical intervention. However it is accompanied by a more pronounced motor block, and it has a negative effect on the early activation of maternity patients in the postoperative period. The use of 0.75% solution of ropivacaine hydrochloride provides the most favorable conditions for operative delivery which is confirmed by low estimates of the intensity of pain on the VAS scale, both immediately before surgery and three hours after surgery, the minimum time from the moment of induction to the incision of the skin, ensuring adequate sensory block, the absence of pronounced motor block, and early activation of maternity patients.